(untitled) (Quinto Sol, 2021)
This article analyzes the public health policy of Peronist governors (1946-1955) in Buenos Aires Province. I consider both the government and the opposition treatment to the Ministry of Public Health creation and the construction plans that formed the public health policy. In the second part I focus on the practices related to public management, and the trajectories of ministry officials. Financial and personal resources assigned and the effective expansion of the health services are analyzed. The results suggest that provincial health policy had a significant development but short-term and long-term constraints limited the changes. In addition, legal provisions such as practices referring to traditional health institutions show that the provincial State was conceived as a coordinating entity of the health system rather than a unifying one.